2017
DOI: 10.2166/washdev.2017.073
|View full text |Cite
|
Sign up to set email alerts
|

Take it away: the need for designing fecal sludge disposal services for single-pit latrines

Abstract: 3The Government of Bangladesh is increasingly paying attention to the safe collection and disposal of 4 fecal sludge from pit latrines in rural areas. In this paper, we report on current sludge disposal 5 practices from single-pit latrines, by conducting a survey of 1,091 households with pit latrines in a 6 rural subdistrict of Bangladesh. Almost all households were using their pits, and 90% reported that 7 hiring pit emptiers to empty the pit for reuse was the dominant pit management practice. However, 8 90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The high water tables characteristic of large parts of Bangladesh also mean that aerobic treatment potential inside pit latrines may be rather limited. Previous fieldwork suggested that pit contents retained high levels of pathogens, particularly helminth eggs, for a long period [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high water tables characteristic of large parts of Bangladesh also mean that aerobic treatment potential inside pit latrines may be rather limited. Previous fieldwork suggested that pit contents retained high levels of pathogens, particularly helminth eggs, for a long period [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The total volume of sludge which needs to be moved to meet 100% of demand for emptying also needs to be estimated. In this paper, the volumes of fecal sludge to be transported in Bhaluka were estimated based on earlier studies reported in [ 7 ].…”
Section: Estimating Costs For Emptying and Transport Of Fecal Sludgementioning
confidence: 99%
See 1 more Smart Citation
“…This is a critical issue for CBS providers because regular neighbourhood visits are necessary for the safe and hygienic collection of waste. This reflects wider recognition in the literature that the operational efficiency of transport arrangements is a major barrier for road-based faecal sludge management (FSM) systems (Kennedy-Walker et al 2016;Balasubramanya et al 2017). It is worth noting also that regular visits by a CBS provider are beneficial for fostering positive relationships with the community being served (Moya et al 2019).…”
mentioning
confidence: 82%
“…Also, even though some studies have suggested that it is best to desludge septic tanks (for example) every 2-5 years depending on number of users (Gill et al, 2016;Mehta et al, 2019), some systems are not emptied for up to 20 years and end-up with solidified sludge that are really difficult to remove (ISF-UTS and SNV 2019;Mehta et al, 2019). This practice is prevalent in most developing countries due to considerable technological and social obstacles (Mills, 2013;Peal et al, 2014, Kirsch andHammersley-Mather, 2017;Balasubramanya et al, 2017) where sanitation facilities such as latrines/ toilets are mostly constructed poorly with sub-standard materials and limited spaces. Also, desludging vehicles and equipment are hindered due to poor accessibility, high exposure to faecal matter during collection and transportation, as well as blockages from the use of bulk materials from anal cleansing, menstrual hygiene and solid waste disposal (Thye et al, 2011;Nakagiri et al, 2016;Kirsch and Hammersley-Mather, 2017).…”
mentioning
confidence: 99%